1979
DOI: 10.1254/jjp.29.17
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Ester-Type Drugs by the Purified Esterase From Human Intestinal Mucosa

Abstract: Abstract-Esterase from human intestinal mucosa was purified 210 fold by solubilization with Triton X-100, chromatography on DEAF-cellulose, Sephadex G-100 and hydroxy lapatite, and isoelectric focusing. The purified esterase showed a single band by polyacrylamide gel electrophoresis.The molecular weight of the purified esterase was estimated to be about 55,000 by gel filtration on Sephadex G-150, and the isoelectric point was 5.02. The purified esterase was strongly inhibited by diethyl p-nitrophenyl phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, Inoue et al (Inoue et al, 1979a) showed that esterase activity in the dog intestine is very weak and produced no appreciable active band in a disk electrophoresis coupled with staining of esterase activity. On the other hand, esterase activities were observed in the intestines of other species (human, rat, mouse, guinea pig and rabbit) (Inoue et al, 1979b;Prueksaritanont et al, 1996;Mansbach and Nevin, 1998;Imai et al, 2006;Satoh and Hosokawa, 2006) and found to produce a few active bands in an electrophoretic assay.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Inoue et al (Inoue et al, 1979a) showed that esterase activity in the dog intestine is very weak and produced no appreciable active band in a disk electrophoresis coupled with staining of esterase activity. On the other hand, esterase activities were observed in the intestines of other species (human, rat, mouse, guinea pig and rabbit) (Inoue et al, 1979b;Prueksaritanont et al, 1996;Mansbach and Nevin, 1998;Imai et al, 2006;Satoh and Hosokawa, 2006) and found to produce a few active bands in an electrophoretic assay.…”
Section: Introductionmentioning
confidence: 99%
“…1): carboxylesterase (CES), cytidine deaminase (CDA), and thymidine phosphorylase (TP). In humans, CES is mainly expressed in the liver and intestine (Junge et al, 1974;Inoue et al, 1979). CDA is found in most tissues, including the liver and in tumor tissues (Camiener and Smith, 1965).…”
mentioning
confidence: 99%
“…There are, however, only a few reports on the purification and properties of human intestinal esterase and hepatic esterase (3). We have already reported the purification of esterase from human intestinal mucosa (4,5). When esterase from intestinal mucosa has been examined for its action in the metabolism of ester-type drugs in the body, esterase from liver must also be considered.…”
mentioning
confidence: 99%